2015
DOI: 10.1111/pcmr.12398
|View full text |Cite
|
Sign up to set email alerts
|

The role of thioredoxin reductase 1 in melanoma metabolism and metastasis

Abstract: Although significant progress has been made in targeted and immunologic therapeutics for melanoma, many tumors fail to respond, and most eventually progress when treated with the most efficacious targeted combination therapies thus far identified. Therefore, alternative approaches that exploit distinct melanoma phenotypes are necessary to develop new approaches for therapeutic intervention. Tissue microarrays containing human nevi and melanomas were used to evaluate levels of the antioxidant protein thioredoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…Selenium, an antioxidant micronutrient that can support the metabolism of ROS via the selenoproteins thioredoxin reductase and glutathione peroxidase (42), has actually been found to increase risk for non-melanoma skin cancer in high-risk populations (43). Using mice transgenic for hepatocyte growth factor, we previously reported that while a single topical treatment of selenomethionine (SeMet) to neonatal mice 24 h prior to UV-irradiation delayed melanoma formation, continued application of SeMet to the skin of these mice promoted the growth of early-stage tumors (44).…”
Section: Discussionmentioning
confidence: 99%
“…Selenium, an antioxidant micronutrient that can support the metabolism of ROS via the selenoproteins thioredoxin reductase and glutathione peroxidase (42), has actually been found to increase risk for non-melanoma skin cancer in high-risk populations (43). Using mice transgenic for hepatocyte growth factor, we previously reported that while a single topical treatment of selenomethionine (SeMet) to neonatal mice 24 h prior to UV-irradiation delayed melanoma formation, continued application of SeMet to the skin of these mice promoted the growth of early-stage tumors (44).…”
Section: Discussionmentioning
confidence: 99%
“…TrxR2 catalyzes the NADPH-dependent reduction of Trx2, which in its reduced state protects against elevated levels of ROS within the mitochondria 136 . It has been reported that TrxR2 expression is highly elevated in liver cancer 137 , TrxR1 levels on the other hand, the cytosolic isoform, are upregulated in many different cancers including breast 138 , thyroid 139 , prostate 140 , liver 141 , melanomas 142 and colorectal, where strong overexpression of both TrxR and Trx may correlate with overall tumor aggressiveness 143 , perhaps through the HIF-1 pathway 144 . The elevated level of the enzyme is an adaptation to the increased ROS production resulting from the higher metabolic activity of cancer cells 145 .…”
Section: Trx2/trxr2/prx3mentioning
confidence: 99%
“…We also investigated correlations of TrxR activity and various clinical characteristics and features of patients with NSCLCs, such as metastasis, TNM stage, and histologic differentiation. Notably, previous studies have shown that TrxR plays a key role in mediating tumor metastasis 45,59,60 . In this study, the level of TrxR activity also increased significantly as NSCLCs progressed to a metastatic state.…”
Section: Discussionmentioning
confidence: 99%